Pulse Duration Dependent Formation of Laser‐Induced Periodic Surface Structures in Atomic Layer Deposited MoS2 - Malte J. M. J. Becher; Jonas B. Ullrich; Julia Jagosz; Aleksander Kostka; Claudia Bock; Andreas Ostendorf; Evgeny L. Gurevich (Advanced Materials Interfaces)
Abstract In this paper, the formation of laser‐induced periodic surface structures (LIPSS) on atomic‐layer deposited MoS2 layers are studied experimentally. The process parameters (laser fluence and the pulse overlap) corresponding to formation of low‐ and high‐spatial frequency LIPSS as well as ablation and modification of the layers are identified for different pulse durations in the range from 0.2 to 10 ps. The role of the temperature accumulation is evaluated by changing the repetition rate from 0.2 to 2 MHz. The negative accumulation effect, i.e., the ablation of the layers becomes more difficult at higher laser pulse overlaps, is also observed. A simple model explaining the transition between different types of the LIPSS and the decrease of the ablation efficiency with the pulse overlap is suggested.